REAL-TIME AI-AUGMENTED REALITY FOR MOBILE LEARNING: ADVANCING EDUCATIONAL TECHNOLOGY - Sushant Ubale, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
A revolutionary development in mobile learning technology, the combination of artificial intelligence (AI) with augmented reality (AR) produces dynamic and adaptable learning environments. The technical framework, integration architecture, and educational applications of AI-AR systems in learning environments are all examined in this thorough article. The article highlights the critical significance of emerging technologies and future research paths while examining the implementation issues across a range of educational contexts, from technical training to historical site education. It shows how AI-enhanced AR systems allow for real-time content adaption, better student engagement, and tailored learning experiences. The article also discusses the pedagogical and technological difficulties encountered while putting these systems into place, offering possible fixes as well as prospects for further advancements in educational technology.